2023
DOI: 10.3390/jfmk8020081
|View full text |Cite
|
Sign up to set email alerts
|

A Chair-Based Music–Kinetic Combined Exercise Program as an Alternative Approach for Increasing Health, Functional Capacity, and Physical Fitness Indices in Middle-Aged Pre-Menopausal Women

Konstantina Karatrantou,
Theodoros Papavasiliou,
Christos Batatolis
et al.

Abstract: Lately, chairs have been widely used as a cheap, easily accessible, safe, and effective training means in different settings (e.g., in gyms, the house, workplaces, and in rehabilitation). This study investigated the effectiveness of a 10-week chair-based music–kinetic integrated combined exercise program on health, functional capacity, and physical fitness indicators of middle-aged pre-menopausal women. A total of 40 healthy women (40–53 years) were assigned to two groups: exercise (EG) and control (CG). The E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 62 publications
1
2
0
Order By: Relevance
“…Previous studies also showed significant improvement in aerobic capacity following basketball or street basketball (streetball) training in adults with Down syndrome [ 25 ], in adolescents with intellectual disabilities [ 52 , 53 ] and in healthy adults [ 28 , 45 ]. Furthermore, the results of the present study are comparable with other studies, which used different recreational team sport interventions (soccer/football, handball, netball) [ 13 , 14 , 16 , 17 , 22 , 33 ] as well different other exercise activities/programs (i.e., combined exercise programs, Zumba, resistance–functional training) [ 13 , 14 , 67 , 68 , 69 , 70 , 71 ] and found significant improvements in various physical fitness parameters of healthy middle-aged and older individuals.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Previous studies also showed significant improvement in aerobic capacity following basketball or street basketball (streetball) training in adults with Down syndrome [ 25 ], in adolescents with intellectual disabilities [ 52 , 53 ] and in healthy adults [ 28 , 45 ]. Furthermore, the results of the present study are comparable with other studies, which used different recreational team sport interventions (soccer/football, handball, netball) [ 13 , 14 , 16 , 17 , 22 , 33 ] as well different other exercise activities/programs (i.e., combined exercise programs, Zumba, resistance–functional training) [ 13 , 14 , 67 , 68 , 69 , 70 , 71 ] and found significant improvements in various physical fitness parameters of healthy middle-aged and older individuals.…”
Section: Discussionsupporting
confidence: 88%
“…The reduction in blood pressure (to more normal values) following a systematic exercise intervention may eliminate the risk of cardiovascular diseases (i.e., coronary heart disease, cerebrovascular disease, rheumatic heart disease, and other conditions), which are the leading cause of death globally (taking approximately 17.9 million deaths each year) [63]. Several previous studies have shown that different recreational team-sport activities (i.e., football, floorball) [29,64,65] and other combined exercise programs using various modes of exercise [66][67][68][69][70][71] effectively decrease blood pressure (systolic and diastolic) in middle-aged individuals, supporting the results of the present study. Regarding the effect of recreational basketball training on blood pressure, there is limited information in the scientific literature with conflicting results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation